2020
DOI: 10.1111/jop.13115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum synuclein‐γ and squamous cell carcinoma antigen as diagnostic biomarkers in patients with oral squamous cell carcinoma and oral potentially malignant disorders

Abstract: Background Clinical diagnosis and monitoring are crucial to reduce the mortality from oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMDs). It has been demonstrated that synuclein‐γ (SNCG) and squamous cell carcinoma antigen (SCCAg) are highly expressed in patients with OSCC and perhaps participate in OSCC progression. This study analyzed the levels of serum SNCG and SCCAg in OSCC, OPMD, and control patients, and evaluated the diagnostic and clinical value of single and combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In this study, we explored the expression and role of SNCG in OSCC. First, we detected the mRNA and protein expression of SNCG in OSCC and found that SNCG was highly expressed in OSCC tissues, which was consistent with our previous study [ 24 , 25 ]. And our results were consistent with those reported in multiple articles, which indicate that SNCG was highly expressed in a variety of tumors [ 9 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, we explored the expression and role of SNCG in OSCC. First, we detected the mRNA and protein expression of SNCG in OSCC and found that SNCG was highly expressed in OSCC tissues, which was consistent with our previous study [ 24 , 25 ]. And our results were consistent with those reported in multiple articles, which indicate that SNCG was highly expressed in a variety of tumors [ 9 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the difference between our experimental results and database results may be due to different sample sources and ethnic differences, which may require more samples to test. At the same time, we analyzed the correlation between the expression of SNCG in OSCC and clinicopathological features and found that the expression of SNCG was related to differentiation, which was consistent with our previous study [ 24 , 25 ]. Next, we explored the diagnostic value of SNCG in OSCC tissues.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations